1989
DOI: 10.1038/340318a0
|View full text |Cite
|
Sign up to set email alerts
|

Palindromic sequences in heteroduplex DNA inhibit mismatch repair in yeast

Abstract: Although single heterozygous markers in yeast usually segregate during meiosis in a 2:2 ratio, abberant 3:1 segregations occur quite frequently as a result of gene-conversion events. A second type of aberrant segregation, post-meiotic segregation, results from the segregation of two genotypes from a single haploid spore; in yeast such events are detected as sectored spore colonies and usually occur rarely. Post-meiotic segregation is thought to result from the replication of heteroduplex DNA formed during meio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
153
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(162 citation statements)
references
References 17 publications
8
153
1
Order By: Relevance
“…With few exceptions, heterozygous insertion or deletion mutations in yeast cells show very little PMS, suggesting that these single-stranded regions are usually efficiently recognized by cellular mismatch repair systems (9,20). We have previously shown that a mismatch resulting from a heteroduplex formed between a wild-type gene and a gene with a palindromic insertion leads to high frequencies of PMS (19). We interpret this result as indicating that the stem-loop or hairpin configuration expected for a heterozygous palindromic insertion in a heteroduplex is inefficiently recognized by cellular mismatch repair systems.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…With few exceptions, heterozygous insertion or deletion mutations in yeast cells show very little PMS, suggesting that these single-stranded regions are usually efficiently recognized by cellular mismatch repair systems (9,20). We have previously shown that a mismatch resulting from a heteroduplex formed between a wild-type gene and a gene with a palindromic insertion leads to high frequencies of PMS (19). We interpret this result as indicating that the stem-loop or hairpin configuration expected for a heterozygous palindromic insertion in a heteroduplex is inefficiently recognized by cellular mismatch repair systems.…”
Section: Resultsmentioning
confidence: 87%
“…The plasmid pDN9 was constructed by cloning a XhoI-BglII fragment of the HIS4 gene in BamHI-SalI-treated YIp5 (19). The plasmid pDN11 was constructed by allowing the palindromic oligonucleotide DNO14 to self-anneal and then inserting the annealed product into the SalI site of pDN9; this Sall site is within the HIS4 coding sequence (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mutant his4-lop and his4-lopc are 26 bp palindromic insertions that result in inefficiently-repaired mismatches (61). Only those markers that are different from the haploid progenitor strains are shown.…”
Section: Jdm213mentioning
confidence: 99%